Y+(-8)=-23

Simple and best practice solution for Y+(-8)=-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+(-8)=-23 equation:


Simplifying
Y + (-8) = -23
Y + -8 = -23

Reorder the terms:
-8 + Y = -23

Solving
-8 + Y = -23

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + Y = -23 + 8

Combine like terms: -8 + 8 = 0
0 + Y = -23 + 8
Y = -23 + 8

Combine like terms: -23 + 8 = -15
Y = -15

Simplifying
Y = -15

See similar equations:

| 24-x=42 | | 4x+5=2(3x+25) | | 6x-2=2x-10 | | (3x+8)(8x+7)=0 | | y=-0.50*40+121 | | y=-0.50*30+121 | | y=-0.50*20+121 | | 2x+48=322 | | 119=6x+17 | | 1500x=20x | | 1400+x=41900 | | 2x^2+4x-47=0 | | -16t^2+t+25=0 | | 2y^2+56=0 | | a+2b=-4 | | a+8b=8 | | 5x+1=-(x-7) | | 18-0.7(s-15)=0.8(9s-15) | | 16-x+36=47 | | 9m-2(1-m)= | | y^2-3y=7 | | 0.12(6)0.02x=0.04(6+x) | | 8*12+6y=48 | | 6x-29-28=9 | | 2n^2+37n-19=0 | | v^2-8v+7=0 | | (6b^3+3b^2+8)-(2b^3-8b^2+6b-5)= | | 6x-29+28=9 | | 2x^2-39x+19=0 | | 8*0+6y=48 | | x+13-26+5=179 | | 3x^3+x-2=0 |

Equations solver categories